2016
DOI: 10.4102/hts.v72i4.3564
|View full text |Cite
|
Sign up to set email alerts
|

Hoist by our own petard: Backing slowly out of religion and development advocacy

Abstract: There has been a massive advocacy movement over the last 15 years that has sought to advance the case of religion into view of decision-makers in the international development sector. This advocacy effort has been dispersed and not centrally organised, and is made up of the efforts of multiple development actors, religious institutions, researchers and others. This article shows how this advocacy approach has been highly successful in increasing acceptance of the fact that religion is relevant to development, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…Despite the proliferation of partnership guidelines within the realm of international development and donor organisations, and despite the rapid expansion of academic literature on religion and development since the turn of the millennium (see, among others, Carbonnier, 2013;Clarke et al, 2007;Clarke, 2013;Deneulin & Bano 2009;Deneulin & Rakodi, 2011;Fountain, 2013;Jones & Petersen, 2011;Levy, 2013;Lunn, 2009;Marshall & Van Saanen, 2007;Marshall, 2013;Olivier 2016;Rakodi, 2012;Smith, 2017;Tomalin, 2013Tomalin, , 2015Tyndale, 2006), the subject of the methodology for engaging development policy and practice alongside religion remains little explored. 4 International development organisations have a practical methodological approach for engaging with religion, particularly through establishing certain principles (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the proliferation of partnership guidelines within the realm of international development and donor organisations, and despite the rapid expansion of academic literature on religion and development since the turn of the millennium (see, among others, Carbonnier, 2013;Clarke et al, 2007;Clarke, 2013;Deneulin & Bano 2009;Deneulin & Rakodi, 2011;Fountain, 2013;Jones & Petersen, 2011;Levy, 2013;Lunn, 2009;Marshall & Van Saanen, 2007;Marshall, 2013;Olivier 2016;Rakodi, 2012;Smith, 2017;Tomalin, 2013Tomalin, , 2015Tyndale, 2006), the subject of the methodology for engaging development policy and practice alongside religion remains little explored. 4 International development organisations have a practical methodological approach for engaging with religion, particularly through establishing certain principles (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…development organisations on the one hand, and 'faith' communities on the other, as if they were separate entities, with the latter to be used for the former's ends. This division between 'secular' and 'religious' has been questioned in the literature (see Ager and Ager, 2011;Calhoun et al, 2011;Deneulin & Bano, 2009;Hovland, 2007;Leurs, 2012;Linden, 2007;Olivier 2016;Smith, 2017…”
Section: Introductionmentioning
confidence: 99%
“…This has not been entirely unproblematic because some of these activities have bypassed the state. Important questions have been raised about what sets faith-based providers apart from other providers in a country where the majority of the population is religious (Olivier, 2016;Tomalin, 2012). Roman Catholics account for 38.5% of the population, Protestants 26.3%, Muslims 20.9%, other Christian denominations 4.5%, with the rest animist of 'non-believers'.…”
Section: Faith-based Health Providers and Health Professional Schoolsmentioning
confidence: 99%
“…There has been an increase in the studies related to religion and development, religion and healing, and/or health and religion as an inspiration for political change especial in the early 20th century through to post-colonial Africa (Olivier 2016). Recent studies in Sub-Saharan Africa have shown that the majority of believers consider religion as an important part of their life (Kar 2008;Levin 2009), and the number of religious believers within the world religions is growing faster in the Global South than the West (Freeman 2012) partly due to the lack of reliable biomedical healthcare infrastructures.…”
Section: Religion and Healingmentioning
confidence: 99%